2007
DOI: 10.1007/s12043-007-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Computation of surface roughness using optical correlation

Abstract: The laser speckle photography is used to calculate the average surface roughness from the autocorrelation function of the aluminum diffuse objects. The computed results of surface roughness obtained from the profile shapes of the autocorrelation function of the diffuser show good agreement with the results obtained by the stylus profile meter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It was assumed that the values of roughness parameters increase asymptotically with the increasing profile length [81]. The profile line shapes of the ACF intensities are obtained at different heights, and it is shown that the shapes are affected by noise [82], depending on the frequency type of noise [83]. By studying the shape of the ACF, the detection and reduction in selected types (frequencies) of measurement errors (noise) can be significantly improved [84].…”
Section: Applied Methodsmentioning
confidence: 99%
“…It was assumed that the values of roughness parameters increase asymptotically with the increasing profile length [81]. The profile line shapes of the ACF intensities are obtained at different heights, and it is shown that the shapes are affected by noise [82], depending on the frequency type of noise [83]. By studying the shape of the ACF, the detection and reduction in selected types (frequencies) of measurement errors (noise) can be significantly improved [84].…”
Section: Applied Methodsmentioning
confidence: 99%
“…It is needed a translation of the surface or the detector to have an intensity of the speckle field high enough for the calculation. This real time technique has a range of measurement limited to less than 1 µm [ 19 ]; Digital holography: based on optical interference and diffraction. It uses holograms to obtain the intensity and the phase of an object [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is needed a translation of the surface or the detector to have an intensity of the speckle field high enough for the calculation. This real time technique has a range of measurement limited to less than 1 µm [ 19 ];…”
Section: Introductionmentioning
confidence: 99%
“…One of the quality measures that is especially challenging for online examination is surface roughness of machined parts. Surface roughness is defined as an amplitude value measuring the vertical heights of the surface deviations from a reference line [1]. Inadequate surface roughness of machined parts can significantly affect the functionality of a product and can lead to a premature failure.…”
Section: Introductionmentioning
confidence: 99%